Єврейська громада Буковини та історичні виклики «епохи сталінізму» 1948-1953 рр. - Яворська, Ірина Тодорівна; Yavorska, Iryna T. (Східноєвропейський національний університет ім. Лесі Українки, 2014)
В статті описуються проблеми, з якими довелося зустрітися єврейській громаді Буковини у повоєнне десятиліття, пов’язаних з появою держави Ізраїль та початком «холодної війни». Автором проаналізовано причини, хід проведення, масштаби та особливості ідеологічної кампанії та репресивні акції, направлені проти єврейських громадських, культурних та літературних організацій, сконцентровано увагу на подіях та долях учасників подій. Упорядкувавши маловідомі факти з життя єврейської громади Буковини автор вважає, що антисемітизм в 1948-1953 рр. носив латентний та обмежений характер, використовувався головним чином як засіб маніпулювання номенклатурою та тиском на інтелектуальний прошарок єврейської громади. The research paper describes a problem related to the formation of the state of Israel and the beginning of the “Cold War” which the Jewish community of Bukovina had to deal with in the postwar decade. The author analyzes the causes, realization, scope and features of the ideological campaign and repressive acts directed against the Jewish community, cultural and literary organizations; the attention is focused on the events and of fates of the participants of those events. Having arranged the little-known facts of the life of the Bukovinian Jewish community, the author believes that anti-Semitism in 1948-1953 could be characterized as latent and limited, used primarily as a means of manipulation of the high-ranking functionaries and pressure on the intellectual part of the Jewish community. “High-flown” propagandistic campaign and anti-Jewish publications in Bukovinian media were aimed at intimidation of the population, at the same time fueling domestic and socio-political anti-Semitism. The lack of Soviet emigration law and the right of exit from the country nullified all Bukovinian people’s attempts to immigrate to Israel.
The Jewish community of Bukovina and historical challenges of the "era of Stalinism" in 1948-1953.
Keywords: інтелігенція єврейського походження; репресії; антисемітизм; сіонізм; космополіти; асиміляція; intellectuals of Jewish origin; repression; anti-Semitism; Zionism; cosmopolitans; assimilation